Transformational Leadership and Innovative Work Behavior: Mediating Roles of Organizational Culture, Self-Efficacy, and Work Engagement in West Kalimantan State Polytechnics - Wahyudi, Wahyudi (Jurnal Pendidikan Progresif, 2024)
Transformational Leadership and Innovative Work Behavior: Mediating Roles of Organizational Culture, Self-Efficacy, and Work Engagement in West Kalimantan State Polytechnics. Objective: This research explores the impact of transformational leadership (TL) on fostering innovative work behavior (IWB) among teaching staff at State Polytechnics in West Kalimantan. The study delves deeper by examining the mediating roles of organizational culture (OC), self-efficacy (SE), and work engagement (WE) in this dynamic relationship. Methods: Utilizing a quantitative research design, data were collected through surveys from 220 respondents across various State Polytechnics in West Kalimantan. The analysis was conducted using the Structural Equation Modeling Partial Least Squares (SEM PLS) method, allowing for the testing of complex relationships among TL, OC, SE, WE, and IWB. Findings: The findings reveal that TL positively and significantly influences IWB. Furthermore, OC, SE, and WE were identified as critical mediators in the TL-IWB relationship. Notably, WE emerged as the most influential mediator, emphasizing its critical role in bridging the gap between transformational leadership and innovative behavior in educational environments. Conclusion: This study underscores the pivotal role of transformational leadership in cultivating an innovative work culture among teaching staff. For polytechnic leaders, the findings suggest that fostering a supportive OC, enhancing SE, and actively engaging staff in their work are vital strategies to encourage innovation. These insights contribute to the broader literature on leadership and innovation and point to the need for further exploration in diverse educational contexts. Keywords: transformational leadership, innovative work behavior, organizational culture, self-efficacy, work engagement.DOI: http://dx.doi.org/10.23960/jpp.v14.i2.202484